T lymphocyte responses against human parvovirus B19: small virus, big response. - Klenerman, P; Tolfvenstam, T; Price, D; Nixon, D; Broliden, K; Oxenius, A (2002)
Parvovirus B19 elicits both humoral and cellular immune responses. Recently some advances have been made in determining the frequencies, peptide targets and function of virus-specific CD8+ T lymphocyte responses. A single HLA B35-restricted epitope derived from the NS1 protein has been studied so far, but others clearly exist. Surprisingly large, persistent responses have been detected in healthy seropositive individuals, using interferon-gamma ELISpot assays and HLA class I peptide tetramers. Similar techniques are available for exploration of the CD4+ T cell epitopes, although less detail is currently available. Mapping of cellular immune responses against the entire B19 genome (the parvovirus "immunome") is now possible and if similarly large populations are found consistently, this could yield important insight into normal immunological control and abnormalities in B19-related disease.